Fiqh Teacher Strategies in Motivating Learning Students in Fiqh Lessons Class VIII at MTS Aisyiyah Binjai - Qiki Luthpiyah (Indonesian Journal of Education and Mathematical Science, 2022)
This study examines how the process of learning fiqh at MTs Aisyiyah Binjai. In addition, this researcher also examines how the strategy of fiqh teachers in motivating students' learning at MTs Aisyiyah Binjai and examines what are the supporting and inhibiting factors of fiqh teachers' strategies in learning motivation of students at MTs Aisyiyah Binjai. This research uses descriptive qualitative research. By using data collection techniques in the form of observation, interviews and documentation. The purpose of this study is to find out how the process of learning fiqh is, to find out how the strategy of fiqh teachers in motivating student learning at MTs Aisyiyah Binjai and to find out what are the supporting and inhibiting factors of fiqh teachers' strategies in motivating student learning at MTs Aisyiyah Binjai. The analysis used in this study refers to data reduction, data presentation and conclusion drawing. The results obtained from this study are. The importance of implementing good and appropriate learning strategies will be able to foster the spirit of learning fiqh at MTs Aisyiyah Binjai. Conventional methods or strategies applied so far by fiqh teachers cause students to be lazy to study, fall asleep in class, make noise and result in students' learning outcomes of fiqh are not optimal. The strategy used by fiqh teachers in motivating students' learning is by using a cooperative